Diagnosis Banding Kasus Garre's Osteomyelitis - Heru Suryonegoro (Faculty of Dentistry, Universitas Indonesia, 2015)
Garre's Osteomyelitis is a type of Osteomyelitis which occur frequently in clinic. This disease can occur at any age, but most happen in and young adult, and frequently in mandible. Usually patient complaint about pains/hurt and jaw getting bigger and hard on bone jaw surface. Osteomyelitis is more frequently happen at incisive which expand medial and lateral. If the perios tissue inflamed, it tend to build a new bonetissue inside, which only can be seen by Roentgen photo if the cause is apical infection. The infection tissue at the apical of teeth expand through bone surface and reach periosteum which can change periosteum from bone surface. If the expand of the new bone apically, so it will be seen with periapical projection. And if the expand goes laterally, it will be seen with occlusal prejection. It will be discussed about the connection of Garre's Osteomyelitis Roentgen view in various type of projection and its differential diagnose in Roentgen with ostegenic sarcoma and about the other lesion which shown almost the same with it.